A review of epidemiological studies of the health effects of living near or working with electricity generation and transmission equipment. - Coleman, M; Beral, V (1988)
In the last ten years there has been increasing concern that the extremely low frequency (ELF), non-ionising electromagnetic fields emitted by electrical installations and equipment using alternating current at 50-60 Hertz might have long-term effects on health. Studies of the association between disease and residence near installations transmitting or generating electricity and studies of the health of workers in the electrical industry are reviewed. Most of the investigations relate to cancer, although other conditions such as outcome of pregnancy have been studied. The most consistent finding is that electrical workers appear to be at increased risk of leukaemia, especially acute myeloid leukaemia. The effect is small. Combining the results of eleven separate investigations suggests an 18% increase in the risk of leukaemia (RR = 1.18, 95% confidence interval (CI) 1.09-1.29) which is partly or wholly due to a 46% increase in the risk of acute myeloid leukaemia (RR = 1.46, 95% CI 1.27-1.65). It is not clear whether this increase is specific to certain types of work within the electrical industry. Nor is it possible to determine from the available data if the increase in leukaemia is due to electromagnetic fields or to other factors to which electrical workers are exposed. There is no clear association between cancer risk and residence near sources transmitting electricity, although some data suggest that there may be small increases in leukaemia in those living very close to the sources. The relationship between adverse outcome of pregnancy and exposure to sources of ELF electromagnetic fields needs further investigation. Studies of the possible effects of ELF electromagnetic fields on health are hampered by problems in measuring exposure and by the ubiquity of exposure in the community.